The Challenges of Islamic Communication in Facing the Normalization of Romantic Behavior of Teenagers in Banda Aceh City - Mallikatul Hanin; Siti Nurramadani; Raysan Al-Hakim; Muhammad Yusuf. Aj; Taufik (Wardah, 2025)
This study aims to analyze the challenges of da’wah communication in responding to the normalization of romantic behavior among adolescents in Banda Aceh. The research focuses on identifying the forms of romantic behavior, the responses of da’wah actors, and the barriers that arise in delivering moral messages within the youth digital culture. This study employs a descriptive qualitative approach, with data collected through in-depth interviews and social observation. The research informants consist of five individuals, including one young da’i and four adolescents from diverse social backgrounds. The findings reveal that romantic behaviors such as riding in pairs, spending time together privately at cafés, and displaying intimacy on social media are increasingly perceived as socially acceptable. This normalization is driven by digital media influence, popular cultural trends, the weakening of parental supervision, and adolescents’ psychological need for social recognition. Adolescents do not reject religion itself, but rather resist forms of da’wah that are judgmental, rigid, and lacking communicative sensitivity. Instead, they prefer da’wah that is persuasive, conversational, uses contemporary youth language, and is disseminated through social media and direct engagement in their social environment. The analysis employs the Uses and Gratifications Theory, which explains that adolescents actively select and consume media content based on their psychological and social needs. Consequently, romantic content becomes more attractive than conventional religious communication. The study concludes that the effectiveness of da’wah in the digital era depends on the ability of preachers to adapt their communication strategies, optimize the use of social media, and provide alternative gratifications that align with Islamic values.